SCO and India-Pakistan Conflict - Ms. Huma Rehman; Muhammad Faisal (CISS Insight Journal, 2015)
In last 15 years SCO has evolved into a regional security organization with focus on combating terrorism and enhancing regional stability by enhancing security and confidence building amongst its members. China and Russia are the leading drivers behind the primarily, Central Asian group, with interests spread over Eurasia. In 2015, SCO decided to expand its membership to include India and Pakistan, the South Asian arch‐rivals. SCO had been reluctant to give both rivals permanent membership because of the active nature of their conflict. However, membership of India and Pakistan, brings with it new opportunities. It is for the first time, that, both rivals will join a regional security organization, where, close ally of each is also present, Russia in case of India, and China in respect of Pakistan. Membership of SCO, and presence of China and Russia, will likely lead to emergence of stability and gradual building of trust in security sector, as India and Pakistan will be working together in various fora of the organization. A key focus of SCO is to stabilize the border areas and cooperation among member states to combat terrorism. Islamabad and New Delhi can address their bilateral concerns on these two issues via a multilateral forum and building much needed mutual trust, thus, beginning a new era of cooperation for stability in South Asia.